Underrepresentation of women in exercise science and physiology research is associated with authorship gender - James, J. J.; Klevenow. E. A.; Atkinson, M. A.; Vosters, E. E.; Bueckers, E. P.; Quinn, M. E.; Kindy, S. L.; Mason, A. P.; Nelson, S. K.; Rainwater, K. A. H.; Taylor, P. V.; Zippel, E. P.; et al. (Journal of Applied Physiology, 2023)
Historically, low representation of women participants in exercise science and physiology studies has led to a lack of understanding in the response of women to exercise and therapeutic interventions. We hypothesized that 1) the number of women authors, participants, and editorial board members increased over 30 years (1991-2021) and 2) larger representation of women as editors and authors is associated with more women participants. Gender (man/woman) of editorial board members (n = 394), authors (n = 5,735), and participants (n = 2,984,883) of 972 original research articles with human participants published in 1991 and 2021 was analyzed from three journals: Journal of Applied Physiology, Medicine and Science in Sports and Exercise, and British Journal of Sports Medicine. Between 1991 to 2021, the average percent women per article as participants (21.9 ± 31.7% vs. 36.3 ± 30.3%, respectively, P < 0.001), authors (16.4 ± 22.4% vs. 30.9 ± 24.0%, P < 0.001), and editorial board members (13.3 ± 5.4% vs. 41.5 ± 7.3%, P = 0.006) increased. In 2021, the gender proportion of participants in large datasets was similar (50.2 ± 20.2% women). However, studies with smaller datasets (i.e., <~3,000 participants) included less women (35.6 ± 30.6%). Women participants (%) were less when the last author was a man rather than a woman in 1991 (19.9 ± 29.5% vs. 34.3 ± 42.2%) and 2021 (31.6 ± 27.7% vs. 51.7 ± 33.4%). In 2021, there was a positive correlation between author and participant gender (% women) (r = 0.42, P < 0.001). Our data suggest that the low representation of women in exercise science and physiology research could be resolved with equitable numbers of women authors and editors and by encouraging men authors to study both women and men participants.